2017
DOI: 10.1016/j.jjcc.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of anti-Xa activity and factors related to bleeding events: A study in Japanese patients with nonvalvular atrial fibrillation receiving rivaroxaban

Abstract: Peak AXA level was an independent predictor for bleeding events in Japanese NVAF patients receiving rivaroxaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
4
35
0
1
Order By: Relevance
“…Because macitentan is an inhibitor of P‐gp in vitro , concurrent oral administration of both compounds could impair intestinal efflux of rivaroxaban into the gut lumen and thus accelerate its absorption and shorten t max . High rivaroxaban peak concentrations have been related to bleeding events , but the observed pharmacokinetic trend in this study was small and thus unlikely to be of clinical relevance, suggesting that, from a pharmacokinetic point of view, these drugs can probably be combined without dose adjustment. Moreover, the supposed mechanism of interaction suggests that this effect on absorption will be likely to be mitigated if macitentan is only administered after rivaroxaban C max is reached (i.e.…”
Section: Discussionmentioning
confidence: 71%
“…Because macitentan is an inhibitor of P‐gp in vitro , concurrent oral administration of both compounds could impair intestinal efflux of rivaroxaban into the gut lumen and thus accelerate its absorption and shorten t max . High rivaroxaban peak concentrations have been related to bleeding events , but the observed pharmacokinetic trend in this study was small and thus unlikely to be of clinical relevance, suggesting that, from a pharmacokinetic point of view, these drugs can probably be combined without dose adjustment. Moreover, the supposed mechanism of interaction suggests that this effect on absorption will be likely to be mitigated if macitentan is only administered after rivaroxaban C max is reached (i.e.…”
Section: Discussionmentioning
confidence: 71%
“…In the clinical pharmacology and biopharmaceutics review of the Food and Drug Administration, exponential relationships have been reported for both, AUC and C max , and the risk of major bleeding . In a recent analysis, higher rivaroxaban peak values (defined as anti‐Xa activity 3 h after drug intake), but not trough values (defined as predose anti‐Xa activity), were associated with major and nonmajor bleeding events . Thus, the increase in rivaroxaban AUC and C max caused by ciclosporin might be clinically relevant, despite an only modest increase in rivaroxaban AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban has been approved to be used clinically in the treatment of several thromboembolic disorders, such as prevention of venous thromboembolism after elective hip or knee replacement surgery . Since 2012, rivaroxaban has been used to prevent stroke among patients with nonvalvular atrial fibrillation in Japan …”
mentioning
confidence: 99%
“…7,8 Since 2012, rivaroxaban has been used to prevent stroke among patients with nonvalvular atrial fibrillation in Japan. 9 Rivaroxaban is a narrow-therapeutic-index (NTI) drug characterized by low within-subject variability as 1 of its noticeable properties. Otherwise, the patients will routinely experience toxicity and lack of efficacy.…”
mentioning
confidence: 99%